Effects of Cooperative Learning Method (CLM) on Vocabularies and Grammars in Essay Writing - Wondwosen Tesfamichael Ali (BIRCU, 2019)
The target of this research was to examine whether or not the effects of CLM improved eleventh graders’ essay writing skills in terms of vocabularies and grammars. The quasi-experimental research was employed and the sample population was taken from two sections of eleventh grade. The CLM was implemented in the experimental group after the students had been made to have awareness about it whereas in the control group, the students were taught their lessons based on the usual lesson plan in which the elements of the method were not used. Data were collected through pre- and post-tests. Dependent t-tests were employed to test whether or not there were significant intra-group differences on the vocabularies and grammars in essay writing skills at 0.05 risk levels whereas independent samples t-tests were used to check if there were significant inter-group differences on the vocabularies and grammars in essay writing skills at 0.05 alpha levels. The analyses of the vocabularies and grammars in essay writing skills pre-test of the inter-groups showed that both groups had similar backgrounds in writing vocabularies and grammars in essays at the initial stage of this research. Nevertheless, after the treatments had been given to the experimental research participants, the analyses of the data indicated that the experimental group outscored significantly (p<0.05) the control group in writing vocabularies and grammars in essay writing post-test. This indicates that the effects of CLM brought about changes on the experimental group. Therefore, the major findings of this study reveal that the CLM enabled the participants in the experimental group to show improvements in writing vocabularies and grammars in essays.